BIBLIOMETRIC ANALYSIS OF RESEARCH TRENDS AND HOTSPOTS IN THE FIELD OF FOREST MUSK DEER (Moschus berezovskii) - Lina Yi; Han Jiang; Fei Hong; Yele Zhang; Jin Bai; Defu Hu (Journal of Animal and Plant Sciences, 2025)
The forest musk deer (FMD) (Moschus berezovskii) represents an endemic and endangered species in East Asia, valued for biodiversity conservation and musk economy. In recent decades, various research has investigated the ecology and biology of FMD. However, a bibliometric analysis is currently missing. This work,for the first time, elucidates the current research trends and hotspots of FMD by analyzing annual publication volume, citations, samples, and keywords from FMD-related publications in two prominent databases: the Web of Science(WoS),and the Chinese National Knowledge Infrastructure (CNKI). The results reveal that (1)both WoS and CNKI publications exhibit fluctuating growth patterns, with CNKI initiating earlier (in 1958) than WoS (1990), however, WoS publications have recently surpassed CNKI. (2) Highly cited WoS articles primarily concentrate on the micro-ecology of captive FMD, whereas highly citedCNKI literature highlights the macro-ecology of wild FMD.(3) CNKI research encompasses a broader array of samples compared to WoS studies.(4) The Citespace keyword timeline maps indicated that WoS research centered on subjects such as “microsatellite loci” and “gut microbiota,” while CNKI studies prioritized themes like “camera trap” and “musk,” alongside a global emphasis on the “musk gland.” Research on FMD reveals significant developmental potential,yetnumerous areas remain underexplored. The current FMD study mostly focuses on disease mechanisms and musk secretion in captive populations. However, research on ecology and the conservation of wild populations is seriously lacking. Future studies should focus on key research areas such as FMD rewilding and reintroduction programs, non-invasive sampling techniques, synthetic musk, and gut probiotics. Pertinent research will inform conservation and sustainable utilization practices for FMD.
Keywords: Forest musk deer; Moschus berezovskii; Web of Science; Chinese National Knowledge Infrastructure; Citespace